INTEGRATING AI AND IOT IN SOLAR POWER SYSTEMS FOR IMPROVED MONITORING AND PREDICTIVE MAINTENANCE - Syed Zain Mir,; Muhammad Kashif Majeed,; Muhammad Hassam Shakil Siddiqui,; Shahzad Karim Khawer,; Ilyas Younus,; Syed Raheem Shah,; Junaid Alam,; Anas Shahid, (Spectrum of Engineering Sciences, 2025)
An AIOT Based solar power monitoring system consists of a solar panel, sensors, microcontroller, Wi-Fi module, server and a computer or smart phone to visualize real time parameters, in an AIOT based solar monitoring system solar panels harness sun light from sun and convert it into DC voltage. This dc voltage is stored in batteries for later use and can be converted into ac by using inverters and to be connected to your load. By using this system, we can measure and monitor the real time output parameters of our solar system, such as solar power, solar voltage, solar current and in software side in dashboard many modules and functionalities are added like battery life predication, weather predication using google API, maintenance and power generation predication. In this some module use AI algorithm like Machine Learning Algorithm to predicate battery life before taking some input from user. This system is built to increase in the power generation and reduce the maintenance cost.